Pengembangan E-Modul Interaktif Teks Prosedur Berbasis Budaya Lokal untuk Meningkatkan Literasi Multikultural Siswa Fase D - Sanrais Josua Saragih; Wisman Hadi; M Oky Fardian Gafari (Varied Knowledge Journal, 2026)
This study aimed to develop a local culture-based interactive e-module on procedural texts that is valid, practical, and effective in improving the multicultural literacy of Phase D students at SMP Negeri 6 Medan. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were seventh-grade students of SMP Negeri 6 Medan. Data were collected through observations, interviews, expert validation questionnaires, student response questionnaires, and pretest-posttest assessments. The results indicated that the developed product was a digital flipbook-based interactive e-module containing procedural text materials integrated with the local culture of North Sumatra and supported by images, videos, interactive quizzes, drag-and-drop activities, glossaries, and learning exercises. The validation results showed that the e-module was highly feasible, with a material expert validation score of 89.2% and a media expert validation score of 92.5%. Practicality testing yielded scores of 87.5% in the small-group trial and 91.7% in the large-group trial, both categorized as highly practical. The effectiveness of the e-module was demonstrated by the improvement in students’ multicultural literacy, with the average score increasing from 61.62 in the pretest to 82.34 in the posttest and an N-Gain score of 0.54 (moderate category). Furthermore, students’ procedural text learning outcomes improved with an N-Gain score of 0.58 (moderate category). Therefore, the local culture-based interactive procedural text e-module is considered feasible, practical, and effective as a digital learning resource for enhancing the multicultural literacy of Phase D students.